ANALYSIS OF READINESS FOR SPECIAL ECONOMIC AREAS MARITIME INDUSTRY SECTOR (STUDY OF CASE OF LAMONGAN DISTRICT) - Putra, Qomaruddin Siroh; Hadi, Khrisno Hadi; Salahudin, Salahudin (Journal of Local Government Issues, 2019)
Some efforts have been made to develop economic potential in the region by implementing Special Economic Zones which have been regulated in Law No. 39 of 2009 concerning Special Economic Zones. One of the regions included in the criteria in the Special Economic Zone is the Lamongan Regency, because Lamongan Regency itself has good maritime potential and is also included in the criteria for special economic zones and also Lamongan Regency itself proposed by the East Java Provincial Government after the birth of the Law. Special Economic Zone Issues for 2009. This research was conducted by using a type of qualitative descriptive research and analyzing qualitative data about the Regional Readiness of Lamongan Regency in the Framework of the Establishment of a Special Economic Sector in the Maritime Industry Sector. In this study the theory used is the theory of special economic zones, the acceleration of local economic development. The results of this study are that some aspects have been fulfilled even though some are still being sought and then completed. Some of these aspects are first, the land readiness that has been available for 500 hectares of land is in accordance with the RTRW that has been established by the Regional Government. Second is the readiness of infrastructure in this case there are several aspects, namely land transportation network, electricity network, telecommunications network, sea port, raw water source. Besides that the readiness of Human Resources (HR) has been running several programs to print competent human resources in the field of maritime industry.Keywords: Readiness, Special Economic Zones, Maritime Industry.